Issue Information. Issue 1 (January 2017) - Unknown
Abstract : Cover Image Left: Taraxacum platycarpum, a native dandelion. Right: Taraxacum offi cinale, a naturalized dandelion. Photographs by Fumio Yoshie, Senshu University Campus, Kawasaki, Japan. Abstract : Cover Image Left: Taraxacum platycarpum, a native dandelion. Right: Taraxacum offi cinale, a naturalized dandelion. Photographs by Fumio Yoshie, Senshu University Campus, Kawasaki, Japan.